Recurrent myelin oligodendrocyte glycoprotein⁃IgG⁃associated optic neuritis⁃encephalomyelitis: one case report - Jing SHA (Chinese Journal of Contemporary Neurology and Neurosurgery, 2020)
DOI:10.3969/j.issn.1672⁃6731.2020.10.006